2014
DOI: 10.1159/000361020
|View full text |Cite
|
Sign up to set email alerts
|

Presence of an Umbilical Artery Notch in Monochorionic/Monoamniotic Twins

Abstract: Objective: To examine the association between an umbilical artery notch and fetal deterioration in monochorionic/monoamniotic (MC/MA) twins. Methods: Six MC/MA twin pregnancies were admitted at 24-28 weeks of gestation for close fetal surveillance until elective delivery at 32 weeks or earlier in the presence of signs of fetal deterioration. Ultrasound (US) examinations were performed twice weekly. The presence of cord entanglement, umbilical artery notch, abnormal Doppler parameters, a non-reassuring fetal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…59 A small cases series has also shown that the presence of a notch in umbilical artery waveform is not associated with an adverse perinatal outcome. 61 Furthermore, even in cases complicated with severe TTTS requiring laser surgery, survival rate remains at 75%, 62 confirming a better perinatal outcome for MCMA pregnancies than previously reported.…”
Section: Zygosity Vs Chorionicitymentioning
confidence: 53%
“…59 A small cases series has also shown that the presence of a notch in umbilical artery waveform is not associated with an adverse perinatal outcome. 61 Furthermore, even in cases complicated with severe TTTS requiring laser surgery, survival rate remains at 75%, 62 confirming a better perinatal outcome for MCMA pregnancies than previously reported.…”
Section: Zygosity Vs Chorionicitymentioning
confidence: 53%
“…A systematic review including a total of 114 monoamniotic twin sets (228 fetuses) with cord entanglement concluded that cord entanglement does not contribute to prenatal morbidity and mortality in monoamniotic twin pregnancy. Moreover, the presence of an umbilical artery notch, without other signs of fetal deterioration, is not indicative of an adverse perinatal outcome ( EVIDENCE LEVEL: 2– ).…”
Section: Complications Unique To Monochorionic Twin Pregnancymentioning
confidence: 99%
“…The incidence of mortality varied according to gestational-age window. IUD occurred in 4.3% (95% Kristiansen (2015) 18 Prefumo (2015) 19 Anselem (2015) 20 Van Mieghem (2014) 21 Murata (2013) 23 Suzuki (2013) 24 Aurioles-Garibay (2014) 22 Dias (2011) 25 Quinn (2011) 26 Assuncao (2010) 27 Baxi (2010) 28 Hack (2009) 29 Arabin (2009) 30 Heflin (2008) 31 Cordero (2006) CI, 2.8-6.2%) of cases at 24-30 weeks, 1.0% (95% CI, 0.6-1.7%) at 31-32 weeks and in 2.2% (95% CI, 0.9-3.9%) at 33-34 weeks of gestation, while there was no IUD, either single or double, from 35 weeks of gestation, although the sample size was small (Table 3, Figure 3). sIUD and dIUD occurred, respectively, in 2.0% (95% CI, 1.4-2.7%) and 2.9% (95% CI, 1.8-4.2%) of twins at 24-30 weeks, 0.6% (95% CI, 0.2-1.1%) and 0.7% (95% CI, 0.3-1.2%) at 31-32 weeks, and 1.0% (95% CI, 0.4-1.9%) and 1.6% (95% CI, 0.6-3.0%) of cases at 33-34 weeks of gestation.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…When analyzing those studies reporting the etiology of IUD, 29.5% (95% CI, 13.5-48.8%; I 2 = 55.2%) of the overall losses were due to TTTS or growth restriction, while 54.0% (95% CI, 37.1-71.3%; I 2 = 42.8%) were unexpected IUD. Furthermore, from 31 weeks of (a) (b) Saccone (2019) 16 Prefumo (2015) 19 Van Mieghem (2014) 21 Murata (2013) 23 Aurioles-Garibay (2014) 22 Quinn (2011) 26 Baxi (2010) 28 Hack (2009) 29 DeFalco (2006) 34 Heyborne (2005) 35 Ezra (2005) 36 Allen (2001) 39 Combined Saccone (2019) 16 Kristiansen (2015) 18 Anselem (2015) 20 Van Mieghem (2014) 21 Dias (2011) 25 Hack (2009) 29 Heflin (2008) 31 Pasquini (2006) 33 DeFalco (2006) 34 Heyborne (2005) 35 Ezra (2005) 36 Demaria (2004) 37 Sau (2003) 38 Allen (2001) gestation, all IUDs included in the present systematic review were reported to be unexpected and not the consequence of a chronic condition that can be potentially identified in utero. Twenty studies reported the incidence of mortality in pregnancies managed mainly as inpatients and/or those followed up as outpatients.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation